2021
DOI: 10.1002/pc.26337
|View full text |Cite
|
Sign up to set email alerts
|

Damage analysis of combined continuous and discontinuous thin‐ply carbon/glass hybrid composite using acoustic emission

Abstract: Thin-ply hybrid composite is an attractive technology for realizing highperformance ductile composites (carbon and glass). However, the continuous carbon (CC) layers are limited to a thickness that can only emit small fracture energies to achieve pseudo-ductility, compromising the mechanical performance of the laminates due to the low carbon/glass ratio. To solve this problem, four different lay-up architectures of partially discontinuous carbon (DC) and angled carbon layers were coupled with continuous glass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…[ 24 ] A number of studies have been reported over the years to achieve pseudo ductility in FRPCs. [ 16,25 ] Promising results of hybridization have also been reported for other materials. [ 26–30 ] Another promising approach for hybridizing is the use of two different type of weave structures which can significantly reduce the resin‐rich areas because of different weave architecture (i.e., nesting effect).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…[ 24 ] A number of studies have been reported over the years to achieve pseudo ductility in FRPCs. [ 16,25 ] Promising results of hybridization have also been reported for other materials. [ 26–30 ] Another promising approach for hybridizing is the use of two different type of weave structures which can significantly reduce the resin‐rich areas because of different weave architecture (i.e., nesting effect).…”
Section: Introductionmentioning
confidence: 81%
“…Hybrid FRPCs generally refer to a class of composite materials with two different types of fibers reinforced within a single polymer matrix. [11][12][13][14][15][16][17] Hybridization of high-strain fibers, for example, glass fiber (GF) and high-strength fibers such as carbon fiber (CF) can ensure high strength as well as high failure. [18,19] Carbon fibers are wellknown for their high strength, which is even higher than that of some metals, but suffer from brittleness and exhibit low tensile failure strain ranging from 0.4% to 2.4%.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other detailed studies have investigated the effect of aging, [22] electrical resistance [23] and the use of hybrid thin ply composites. [24] Composites have been widely studied in structural joints. [25][26][27] Thin-plies also represent a promising approach to improving the performance of adhesively bonded composite joints due to their ability to enhance the off-axis performance of composites and postpone delamination.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, other detailed studies have investigated the effect of aging, [ 22 ] electrical resistance [ 23 ] and the use of hybrid thin ply composites. [ 24 ]…”
Section: Introductionmentioning
confidence: 99%
“…8-14 These pseudo-ductile composites can either be all carbon, 8 quasi-isotropic carbon/glass hybrid, 9,10,13 aligned carbon/glass hybrid via High-Performance Discontinuous Fiber method, 11 orientation dispersed hybrid, 12 or combined discontinuous and CC with glass hybrid. 14,15 The models designed to predict pseudo-ductility are limited to analytical models that can predict three types of instances. 1,2,11,16,17 These instances are the hybrids containing two materials which are either continuous UD materials, 1,16 continuous UD coupled with discontinuous UD materials, 2 or angle-ply laminates.…”
Section: Introductionmentioning
confidence: 99%